COVID-19 Vaccination While Fasting in Islamic Perspective - Yosi Permatasari (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This paper examines the covid-19 vaccination from an Islamic perspective. The method used in this research is descriptive-qualitative method, and is included in the literature research (library research). The process of collecting data in this study is to make observations, in the sense of tracking various references that have relevance to the focus of the study, both from books, articles, and so on that function to support these data. From the study conducted, it can be seen that vaccination is a preventive measure so as not to contract the Covid-19 virus. The use of vaccines to prevent disease is permissible according to Islamic teachings as long as they meet halal products, maintain halalness, and do not use basic ingredients that are forbidden by Islamic teachings. However, there is also an opinion which states that an unclean substance that changes (by istihalah) into another new substance, is considered holy. This opinion is more appropriate, especially when applied in the context of the use of this COVID-19 vaccine. Regarding whether or not fasting is canceled due to vaccination, scholars have different opinions. However, the majority (Jumhur) stated that the Covid-19 vaccination by intramuscular injection does not invalidate fasting